PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS INKUIRI TERBIMBING BERBANTUAN SIMULASI PHET DALAM PEMBELAJARAN IPA - Sumarauw, Jounne Maya; Ibrahim, Muslimin; Prastowo, Tjipto (Jurnal Penelitian Pendidikan, 2017)
This research aims to develop learning materials based on a guided inquiry-based model and a PhET-assisted learning process which are valid, practical, and effective. The development of learning materials utilized a 4D model without dissemination. The developed learning materials were tested using one group pretest-posttest design at Grade 8, SMPN 3 Airmadidi, North Minahasa in Semester 1 the 2016/2017 Academic Year. Data collection were performed using validation, observation, written test, and questionnaire. The collected data were analyzed using descriptive quantitative and qualitative techniques. The results show that: (1) the validity of developed learning materials which include lesson plan, worksheet, student book, and assessment instrument is achieved; (2) practicality in terms of adherence to lesson plans categorized practical, student activities in learning have reflecting activities that correspond to the stage of guided inquiry-based learning, the difficulties encountered in learning activities that students have not been accustomed to follow guided inquiry-based learning method and use of PhET; (3) student’s responses are effective with respect to the developed learning materials used in class, indicating that the materials are effective for students in mastery learning in terms of cognitive, attitude, and skill aspects. Based on research findings and the corresponding analyses, the developed learning materials are appropriate in terms of validity, practicality, and effectiveness for using of science learning in class.